Blockchain Education: as a Challenge in the Academic Digitalization of Higher Education - Rahardja, Untung (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
Over time, there haven't been many significant challenges to the higher education model. Even if the organization of lectures and learning experiences has changed due to the incorporation of increasingly sophisticated technologies, study themes are still evolving. The work being given here is an analysis of blockchain technology and its potential applications in the field of education, with a focus on the potential for upending the current value chain of academic institutions. Institutions act as central authority for providing and approving student knowledge as well as as a bridge between professors and those who would benefit from it (students). The main advancement of blockchain technology is the unbreakable digital transaction ledger, which can record almost any type of value exchange. They open up new possibilities when paired with other cutting-edge technologies like the internet of things and big data. They provide new opportunities for the decentralized sharing of education and the recording of knowledge and skills when paired with other cutting-edge technologies, such as the internet of things and big data. The end results include a thorough examination of the advancement of blockchain technology for educational purposes and a forecast of potential disruptions for educational institutions. There are currently apps targeted at decentralizing educational institutions using blockchain technology, which is developing at an ever-increasing rate. In the interim, a wider group of adepts continue to adopt the technique.